The placebo effect does not enhance sprinting or jumping performance in trained athletes - Agudo-Ortega, A.; Muñoz de la Cruz, V.; Valero, F.; Morallón, P.; González-Mohíno, F.; Salinero, J. J. (Journal of Human Sport & Exercise, 2025)
This study aimed to analyse the placebo effect associated with caffeine on the performance of sprinters in a 60-meter sprint test and a standing triple jump. Methods: Thirteen trained sprinters (7 men, 6 women) volunteered to complete the experimental procedures (22.8 ± 4.7 years, 64.7 ± 6.5 kg and 173.9 ± 6.5 cm). A repeated, randomized, and counterbalanced experimental design was used to compare the effects of the ingestion of a placebo reported as caffeine (placebo) and a control situation where no substance was ingested (control). In both conditions, they completed a standing triple jump, and a 60-meter sprint test and filled out a questionnaire about potential side effects. Results: Performance was similar in placebo and control conditions in the 60-meter sprint test (7.52 ± 0.46 vs. 7.55 ± 0.43 s; p = .49; small d = 0.20) and the standing triple jump (7.28 ± 0.84 vs. 7.28 ± 0.87 m; p = .95; trivial d = 0.02). The most frequent side effects derived from deceptive caffeine ingestion were increased activeness (53.8%), nervousness (23.1%) and insomnia (15.4%). Conclusion: Deceptive caffeine ingestion did not alter performance in sprint and triple jump performance in trained athletes, while some minor side effects appeared. Individual responses to placebo ingestion should be carefully considered before making recommendations for sprint athletes.